A palavra, o trabalho das agulhas e o choro da donzela irmã de Persival d'A demanda do Santo Graal : uma alegoria cristã - Silva, Alessandra Fabrícia Conde da (2008)
Marks the presence of a feminine character – Persival's sister – like allegorical figure and, so, ideological, in A Demanda do Santo Graal. Undertakes a study on the allegory, considering the rhetoric theory on that resource as the universal form of reading that was prosecuted in the Medieval period and that was intending to reproduce the “truth”. Intends to discuss about the conception of the women in the Middle Ages, namely: the view of clerics and the view of the courtesans, by means of the study on the Medieval character and of the feminine social history.